Potential Mechanisms of Melatonin in Osteosarcoma and Bone-Related Neoplasms: Updated Review - Dana, Parisa M.; Sadoughi, Fatemeh; Reiter, Russel J.; Yousefi, Bahman; Asemi, Zatollah (Mini Reviews in Medicinal Chemistry, 2023)
Melatonin (N-acetyl-5-methoxytryptamine) is a secretory product of the pineal gland. A great number of studies have been investigating the functions of this indoleamine in various diseases. Excessive proliferation, reduction in apoptosis, increased angiogenesis, invasion, and metastasis are all processes associated with cancerous tissues. In several cancer types, melatonin is reported to significantly impact these processes. Although bone cancer is relatively rare, it is a serious disease that often becomes metastatic, leading to an unsatisfactory prognosis. In recent decades, significant advances have been made in the therapeutic strategies for bone cancer. Nevertheless, few changes have occurred to patients’ outcomes or therapeutic methods. Currently used therapeutic strategies including chemotherapy and radiotherapy often show serious side effects. Moreover, therapeutic options are not sufficient in certain cases, such as metastatic forms of the disease. Therefore, there is a need for a more precise definition of the molecular pathways and cellular functions associated with bone cancer to find novel therapeutic approaches. With such advances, the development of new effective therapies for patients with advanced stage or metastatic forms of the disease will be achieved, resulting in an improved prognosis. This review summarizes what is known about the functions of melatonin in osteosarcoma and Ewing’s sarcoma. We explain the underlying mechanisms of action by which melatonin serves as an antitumor agent in bone cancer as well as provide an insight into its synergistic effects with other chemotherapeutic drugs.
Keywords: metastalic